The New Residency: What Are the Essential AI Knowledge Requirements for Digital Health Professionals? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The New Residency: What Are the Essential AI Knowledge Requirements for Digital Health Professionals? The rapid integration of Artificial Intelligence (...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care